Islamicate cosmopolitan spirit - Lawrence, Bruce B. (Wiley-Blackwell manifestos, 2021)
Overview : a manifesto in 3 words and 6 chapters -- Islamicate cosmopolitan spirit across time and space -- Eastward into India -- Westward into Spain -- Premodern Afro-Eurasia -- Persianate culture across the Indian ocean -- Islamicate cosmopolitan spirit beyond 2020 -- Conclusion.